A simple angle integration method for the determination of capture reaction cross sections - Michalopoulou-Petropoulou, V.; Lagaki, V.; Axiotis, M.; Foteinou, V.; Lagoyannis, A.; Provatas, G.; Harrisopulos, S. (HNPS Advances in Nuclear Physics, 2019)
In order to determine the cross section of a reaction by the angular distribution method, it is essential to calculate the angular distributions of all secondary transitions that lead to the ground state. This is achieved by analysing spectra from HPGe detectors at various detection angles, which is a time consuming process. In this work, a simpler angle integration method is presented that allows to determine cross sections of capture reactions by measuring spectra at fewer detection angles.